Unreamed Intramedullary Nailing Versus External Fixation for the Treatment of Open Tibial Shaft Fractures in Uganda: A Randomized Clinical Trial. Issue 9 (September 2022) - Kisitu, Daniel K.; O'Hara, Nathan N.; Slobogean, Gerard P.; Howe, Andrea L.; Blachut, Piotr A.; O'Brien, Peter J.; Stockton, David J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To compare unreamed intramedullary nailing versus external fixation for the treatment of Gustilo–Anderson type II and IIIA open tibial fractures admitted to a hospital in rural Uganda. Design: Randomized clinical trial. Setting: Regional referral hospital in Uganda. Patients: Fifty-five skeletally mature patients with a Gustilo–Anderson type II or IIIA open tibia shaft fracture treated within 24 hours of injury between May 2016 and December 2019. Intervention: Unreamed intramedullary nailing (n = 31) versus external fixation (n = 24). Main Outcome Measurements: The primary outcome was function within 12 months of injury, measured using the Function IndeX for Trauma (FIX-IT) score. Secondary outcomes included health-related quality of life (HRQoL) using the 3-level version of the 5-dimension EuroQol instrument (EQ-5D-3L), radiographic healing using the Radiographic Union Scale for Tibia (RUST) fractures score, and clinical complications. Results: Treatment with an intramedullary nail resulted in a 1.0-point higher [95% credible intervals (CrI), 0.1 to 1.9] FIX-IT score compared with external fixation. Results were similar for the secondary patient-reported outcomes, EQ-5D-3L and the visual analog scale component of the EuroQol instrument (EQ-VAS). RUST scores were not different between groups at any time point. Treatment with an intramedullary nail was associated with a 22.1% (95% CrI, −42.6% to 1.7%) lower rate of malunion and a 20.8% (95% CrI, −44.0% to 2.9%) lower rate of superficial infection. Conclusion: In rural Uganda, treatment of open tibial shaft fractures with an unreamed intramedullary nail results in marginal clinically important improvements in functional outcomes, although there is likely an important reduction in malunion and superficial infection. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.